Penerapan Virtual Reality Tour Untuk Inovasi Informasi Pariwisata Berbasis MDLC: Studi Kasus: Dinoland Garut - Latifah, Ayu; Amelia, Nadya (Jurnal Algoritma, 2025)
Tourism is an important sector that supports the economy, creates jobs, and contributes to the country's foreign exchange. However, one of the challenges faced by local attractions, such as Dinoland Garut, is the lack of adequate information and interactive tourism experiences for visitors. This research aims to design a Virtual Reality Tour as an interactive information and promotion media, with a focus on Dinoland Garut. This application is expected to overcome the limitations in the delivery of information and improve the virtual tourism experience. The method used in this research is the Multimedia Development Life Cycle (MDLC), which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. Making Virtual Reality Tour applications is done using 3D Vista software. The results of the test show that this application shows that all application features have run according to their functions and are rated very well by users. Dinoland Garut Virtual Reality Tour application is equipped with informative features, such as details about attractions, ticket prices, and location maps. Thus, this application acts as a digital innovation that is expected to increase the attractiveness of Dinoland Garut and expand the reach of tourism promotion nationally and internationally.